2023
DOI: 10.5195/ijms.2023.1719
|View full text |Cite
|
Sign up to set email alerts
|

Early Point of Care Ultrasound Training in Medical Education, Making the Case with a Case Report

James Wilcox,
Bret Lawson,
Andrew Gauger

Abstract: Background: Point of Care Ultrasound (PoCUS) emerged in the early 1990’s as a promising clinical and educational tool that allows for quicker diagnosis at the bedside.  Our PoCUS program at Indiana University School of Medicine uniquely exposes students to training during their first weeks of medical school, with  training continuing through all 4 years.  Our paper demonstrates the portability and efficiency of PoCUS devices to benefit student run clinics, where vulnerable patients come to seek free medical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The case reported in the article strongly supports their arguments for enhanced point of care ultrasound teaching to be incorporated in medical school curriculums. 30 One review in this edition presents a systematic review of pseudo-chilblains in confirmed cases of COVID-19. 31 The second focuses on medical students' perspective of the operating theatre as a place of learning, exploring negative and demotivating experiences that discourage medical students from operating room attendance.…”
mentioning
confidence: 99%
“…The case reported in the article strongly supports their arguments for enhanced point of care ultrasound teaching to be incorporated in medical school curriculums. 30 One review in this edition presents a systematic review of pseudo-chilblains in confirmed cases of COVID-19. 31 The second focuses on medical students' perspective of the operating theatre as a place of learning, exploring negative and demotivating experiences that discourage medical students from operating room attendance.…”
mentioning
confidence: 99%